101P Results of the NLG2105 phase I trial using the IDO pathway inhibitor indoximod, in combination with radiation and chemotherapy, for children with newly diagnosed DIPG. (15th December 2019) - Johnson, T S; Aguilera, D; Al-Basheer, A; Berrong, Z; Castellino, R C; Eaton, B R; Esiashvili, N; Foreman, N; Heger, I M; Kennedy, E P; Vahanian, N; Martin, W; et al.
Abstract: Background: We conducted a phase Ib dose-confirmation study of indoximod with radiation, followed by indoximod with cyclic temozolomide therapy, to evaluate safety and overall survival (OS) in children with newly diagnosed DIPG (diffuse intrinsic pontine glioma). Indoximod is a small-molecule inhibitor of the IDO pathway that reverses immune suppression imposed by tumor microenvironments. DIPG is a uniformly fatal orphan disease with no curative treatment options. Methods: Children age 3 to 21 years, with newly diagnosed DIPG were eligible for treatment with oral indoximod (38.4 mg/kg/day divided BID, throughout) combined with fractionated conformal radiation therapy (54 Gy in 30 fractions), followed by cyclic oral chemo-immunotherapy using indoximod combined with temozolomide (200 mg/m2/day, days 1-5 of each 28-day cycle). The indoximod dose was the previously determined recommended phase-II dose (RP2D), and the study design called for phase I monitoring to confirm safety of this dose in DIPG patients. Results: Thirteen children (median age 9 years, range 5 to 20 years) with newly diagnosed DIPG were treated using this indoximod-based radio-chemo-immunotherapy regimen. The 12-month OS was 62% (8/13) and estimated median OS was 14.5 months (follow-up range 4.8 to 22 months) with 4 patients remaining in follow-up. This compares favorably to the expected 12-month OS of approximately 45% and median OS of approximately 10.8 months from published historical controls (Kilburn, et al; 2017). Two patients experienced near-complete responses until showing relapse at 7.6 months and 13.3 months of study therapy. Patients were followed with quantitative volumetric analyses of MRIs and serial measurements of peripheral blood inflammatory monocytes, T cell activation, and pro-inflammatory cytokines. The most common adverse events attributed to indoximod were thrombocytopenia, diarrhea, nausea, vomiting, and fatigue. Conclusion: Adding indoximod-based immunotherapy to conventional radiation and chemotherapy for up-front therapy of children with DIPG appears to be well tolerated with improved outcomes. Clinical trial identification: NLG2105, NCT02502708. Legal entity responsible for the study: NewLink Genetics Corporation. Funding: NewLink Genetics Corporation, Alex's Lemonade Stand Foundation, Cannonball Kids cancer Foundation, Beloco Foundation, Eli's Block Party Foundation, Hyundai Hope on Wheels Foundation, Northern Nevada Children's Cancer Research Foundation, CAM Fund, Press On Foundation. Disclosure: T.S. Johnson: Research grant / Funding (institution): NewLink Genetics Corporation. E.P. Kennedy: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: NewLink Genetics Corporation. N. Vahanian: Shareholder / Stockholder / Stock options, Full / Part-time employment, Officer / Board of Directors: NewLink Genetics Corporation. D.H. Munn: Advisory / Consultancy, Shareholder / Stockholder / Stock options, Licensing / Royalties: NewLink Genetics Corporation. All other authors have declared no conflicts of interest.